Biomarker immunoprofile and molecular characteristics in salivary duct carcinoma: clinicopathological and prognostic implications - Santana, Thalita; Pavel, Andrle; Martinek, Petr; Steiner, Petr; Grossmann, Petr; Baněčková, Martina; Skálová, Alena (Human pathology, 2019)
Salivary duct carcinoma (SDC) is one of the most aggressive salivary gland tumors, and prognosis remains poor for most patients. The aim of this study was to investigate the prognostic implications of biomarker immunoprofile in a cohort of SDC and to identify molecular characteristics through next-generation sequencing (NGS) in a subset of cases. Clinicopathological and follow-up information of 25 cases diagnosed as SDC was collected. Immunoexpression of AR, HER-2/neu, GATA3, CK5/6, and MIB1 was analyzed, and ERBB2 (HER-2/Neu) gene amplification was investigated by fluorescence in situ hybridization. Cases were classified under the "SDC revised classification system." Eight SDC cases were analyzed by targeted NGS for detection of gene fusions and variants. Overall survival and disease-free survival were analyzed with Kaplan-Meier curves and Cox regression. Most cases expressed AR (100%), GATA3 (73%), and CK5/6 (76.5%), and 42% expressed HER-2/neu. ERBB2 gene amplification was proven by fluorescence in situ hybridization in 7 of 15 (46%) cases. Apocrine HER2 (AR+/HER2+) subtype was significantly associated with lower overall survival (P = .05). NGS analysis revealed 9 pathogenic mutations in 7 SDC cases, and the most frequently mutated gene was HRAS (4/9) followed by PIK3CA (2/9) and TP53 (2/9). One case (1/9) presented homozygous deletion of locus 9p21 (CDKN2A), and another case (1/9) showed MDM2 amplification. In conclusion, we demonstrated that Apocrine HER2 (AR+/HER2+) is a potential biomarker of poor outcome in SDC. Furthermore, NGS analysis revealed recurrent mutations in SDC.
Keywords: Humans; lidé středního věku; Salivary gland neoplasm; Homozygote; Biomarkers, Tumor; Female; mutace; Aged; dospělí; Salivary Ducts; Salivary Gland Neoplasms; senioři; lidé; Sequence Deletion; NGS; nádory slinných žláz; vývody slinných žláz; Salivary duct carcinoma; nádorové biomarkery; homozygot; Adult; ženské pohlaví; sekvenční delece; Male; Middle Aged; Aged, 80 and over; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; senioři nad 80 let; Immunoprofile; Mutation; mužské pohlaví; duktální karcinom; Carcinoma, Ductal; Prognosis